Thirty-Day Readmissions in Hospitalized Patients Who Received Bezlotoxumab With Antibacterial Drug Treatment for Clostridium difficile Infection - Prabhu, Vimalanand S (Clin Infect Dis, 2017)
We estimated 30-day all-cause and Clostridium difficile infection (CDI)–associated hospital readmissions in participants at high risk of recurrent CDI enrolled in MODIFY I/II. Bezlotoxumab-treated inpatients experienced fewer CDI-associated readmissions compared with placebo-treated inpatients, notably in participants aged ≥65 years and with severe CDI. Clinical Trials Registration. NCT01241552 (MODIFY I) and NCT01513239 (MODIFY II).